Fetal growth and maternal alcohol consumption during early pregnancy. (May 2019) - Reynolds, Ciara M.E.; Egan, Brendan; O'Malley, Eimer G.; McMahon, Léan; Sheehan, Sharon R.; Turner, Michael J.
Abstract: Objective: The relationship between light maternal alcohol consumption and fetal outcome remains contentious and the professional advice women receive is conflicting. The aim of this large epidemiological study was to examine the relationship between fetal growth and maternal alcohol behaviour before and during early pregnancy. Study design: Clinical and sociodemographic details of women who delivered a baby weighing ≥500 g during the eight years 2010-18 were analysed. Details on lifestyle behaviour before pregnancy and at the time of the first antenatal hospital visit were computerised using a standardised questionnaire. Results: Of 68, 925 women, 33.6% abstained from alcohol consumption before pregnancy and 98.4% reported they were abstaining at their first antenatal visit. Only 1.2% reported light consumption (1–2 units/week, median 1.0 IQR 1.0), 0.4% reported moderate/heavy consumption (>3 units/week, median 4.0 IQR 4.0) and 0.3% reported binge drinking (>5 units in one sitting, median 3.0 IQR 4.0). Women who consumed alcohol in binges were more likely to be <30years whereas women who consumed alcohol weekly were more likely to be ≥30years. Women who who consumed any alcohol during early pregnancy were more likely to be multiparous, Irish-born, to have an unplanned pregnancy, to be unemployed, on medications for depression or anxiety, current smokers and abusing illicit drugs. In the absence of persistent smoking or illicit drug abuse, there was no relationship between light alcohol consumption during early pregnancy and the subsequent mean birth weight, preterm delivery (%), small-for-gestational age (%) and mean neonatal head circumference. Conclusion(s): Women who consume alcohol should continue to be advised of the fetal and maternal risks of heavy consumption and, if applicable, of the need to quit smoking and avoid illicit drugs. However, women who have consumed alcohol before realising that they were pregnant or who consumed alcohol in light amounts during early pregnancy, may be reassured that their alcohol consumption did not impact adversely on their baby's growth.